Post-Digital Pedagogy: Deconstructing the Role of Technology in Shaping Contemporary Learning Paradigms - Aziizah Kumala Shanti (PT. Anagata Sembagi Education, 2026)
This study examines post-digital pedagogy as a critical framework for understanding the evolving role of technology in contemporary education. In the post-digital era, technology is no longer viewed as a supplementary tool but as an embedded and complex component that shapes how learning, knowledge, and social interactions occur. This research employs a qualitative approach using a Systematic Literature Review (SLR), analyzing recent peer-reviewed journal articles from databases such as Scopus, Web of Science, and Google Scholar. Data were collected through a rigorous screening process based on relevance and methodological quality, and analyzed using thematic and content analysis to identify key patterns related to pedagogical transformation, technological roles, and socio-cultural dynamics. The findings reveal a paradigm shift from digital integration to pedagogization, where technology is critically examined rather than assumed to be inherently beneficial. Furthermore, learning is increasingly understood as part of a complex socio-technical ecosystem, requiring educators and learners to engage with issues of power, ethics, and digital inequality. The study concludes that post-digital pedagogy necessitates a reconfiguration of educational practices that integrates critical thinking, ethical awareness, and inclusive design to ensure meaningful and transformative learning in contemporary contexts.